Fatty acid metabolism in the calanoid copepod Paracalanus parvus: 1 : Polyunsaturated fatty acids - Moreno, Victor J. (1979)
The metabolic fate of radioactive linoleate and α-linolenate administered to the South Atlantic copepodParacalanus parvus was studied. The wild copepod was able to incorporate the labeled acids dissolved in seawater. The radioactive linoleate was elongated to 20∶2ω6 and 22∶2ω6 and desaturated by a Δ6 desaturase to 18∶3ω6. α-Linolenate was also desaturated by a Δ6 desaturase to 18∶4ω3 and elongated to 20∶3ω3. The copepod was able to convert α-18∶3 to 20∶5ω3 and 22∶6ω3.